Espaço e política : o PCB e suas ações no território brasileiro (1922-1964) - Lepera, Luciano Patrice Garcia (2015)
This research proposes the study of the trajectory of the Brazilian Communist Party (PCB) and its transformations in the territory and society, since the period of its foundation (1922) to the coup d\'État of 1964 - that established a long military dictatorship in the country. With the immigrants, especially in the late 19th century and early 20th century, the anarchist and socialist ideas arrived in Brazil. The Brazil was a predominantly agrarian country and, during the period studied, goes through an urbanization and industrialization process, with major changes in their space. The rising of Brazilian worker class seeks forms of struggle and resistance. In 1922, under the influence of the Russian Revolution (1917), many combat veterans of social struggles founded the one that is the political party of longest life in the country, the PCB. Almost all of the party\'s life - in the temporal cut adopted in this research -, the PCB has kept in illegality, which derives several problems. All over its existence, the PCB adopts different policies, sometimes with a sectarian inclination, sometimes with a character of democratic formation. Due to the different policies and conjectures, the party has times of great popular support, especially in large urban centers, with workers concentrations and land conflict. After the military coup d État in 1964, when the Brazilian bourgeoisie ratified its choice for a capitalism that is dependent of the great powers and authoritative with their workers, the PCB, with a variety of reasons, has greatly diminished his expression on the national political scene.